2020
DOI: 10.1016/j.neuropsychologia.2020.107505
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of working memory to distraction is rhythmic

Abstract: Recent research posits that the cognitive system samples target stimuli in a rhythmic fashion, characterized by target detection fluctuating at frequencies of ~3-8 Hz. Besides prioritized encoding of targets, a key cognitive function is the protection of working memory from distractor intrusion. Here, we test to which degree the vulnerability of working memory to distraction is rhythmic. In an Irrelevant-Speech Task, N = 23 human participants had to retain the serial order of nine numbers in working memory whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Generally, such a relation of pre-stimulus power and perceptual performance has been observed in a wide range of perceptual studies across sensory modalities 8,14,[71][72][73][74][75][76] . However, most studies in the auditory domain reported effects predominantly at lower delta or theta band frequencies 8,9,[11][12][13][14]77 , while a role for alpha band activity is typically discussed for vision and spatial attention paradigms. Though, some studies have linked alpha power to auditory perception [78][79][80] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, such a relation of pre-stimulus power and perceptual performance has been observed in a wide range of perceptual studies across sensory modalities 8,14,[71][72][73][74][75][76] . However, most studies in the auditory domain reported effects predominantly at lower delta or theta band frequencies 8,9,[11][12][13][14]77 , while a role for alpha band activity is typically discussed for vision and spatial attention paradigms. Though, some studies have linked alpha power to auditory perception [78][79][80] .…”
Section: Discussionmentioning
confidence: 99%
“…For statistical analyses, average proportion correct (PC) scores per participant and experimental condition (ranging from 0 to 1) were logit-transformed using an adapted logit-transform proposed by Fox & Weisberg (2019; see also Wöstmann et al, 2020). Single-trial response time (RT) data relative to the onset of the probe screen were removed in case they exceeded 3 seconds and transformed to response speed, quantified as 1/RT.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that a resonance frequency also exists for the vulnerability to distraction. In a recent study, we found that the vulnerability to speech distractors fluctuates at around 2.5 Hz 20 . It might thus be that the frequencies of temporally regular distractors in the current study were either too slow (1.33 Hz in Experiment 3 and 4) or too fast (4 Hz for Experiment 1 and 2) to exert an influence on the eventual memory recall that would differ from temporally irregular distractors.…”
Section: Discussionmentioning
confidence: 91%
“…The current study aimed at filling this gap by investigating how the temporal regularity of distractor sequences influences goal-directed working memory. The onset time of distraction has recently been shown to modulate working memory interference 20 , 21 , demonstrating that temporal features of distractors may play an important role in the susceptibility to distraction in working memory tasks. When it comes to temporal regularity, temporally irregular distractors were recently found to be more disruptive to the detection of deviance in unmasked targets 22 .…”
Section: Introductionmentioning
confidence: 99%